2011
DOI: 10.1038/nmat3123
|View full text |Cite|
|
Sign up to set email alerts
|

Turning aluminium into a noble-metal-like catalyst for low-temperature activation of molecular hydrogen

Abstract: Activation of molecular hydrogen is the first step in producing many important industrial chemicals that have so far required expensive noble-metal catalysts and thermal activation. We demonstrate here that aluminium doped with very small amounts of titanium can activate molecular hydrogen at temperatures as low as 90 K. Using an approach that uses CO as a probe molecule, we identify the atomistic arrangement of the catalytically active sites containing Ti on Al(111) surfaces, combining infrared reflection-abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…Much attention has been devoted to materials that exhibit facile activation and weak binding of hydrogen, as these properties lead to the best energy landscape for storage or chemical reactivity [12][13][14] . Spillover is a common method by which a reagent can be activated at one location and then reacted at another, and it is commonly invoked to explain the synergistic relationship between metals in an alloy or metal/metal oxide mixtures 1,[3][4][5][6][7]12,15 .…”
mentioning
confidence: 99%
“…Much attention has been devoted to materials that exhibit facile activation and weak binding of hydrogen, as these properties lead to the best energy landscape for storage or chemical reactivity [12][13][14] . Spillover is a common method by which a reagent can be activated at one location and then reacted at another, and it is commonly invoked to explain the synergistic relationship between metals in an alloy or metal/metal oxide mixtures 1,[3][4][5][6][7]12,15 .…”
mentioning
confidence: 99%
“…18 The reported system can effectively activate molecular hydrogen similarly to catalysts with precious elements. Chabal and co-workers reported an aluminium catalyst doped with very small amounts of titanium that were subjected to detailed analyses of atomic process on the surfaces using infrared reflectionadsorption spectroscopy and first-principles simulations.…”
Section: Hideki Abementioning
confidence: 96%
“…However,i ftheHcoverage is high and the surfaceA lc an be continuously consumed, Ti tends to segregate to the surface and form as trong bond with the H. As reported by ar ecent study [29] of aT i-doped Al(111)s urface as ap otential heterogeneous catalyst for hydrogenation reactions,i th as been found that the adsorption of Ha nd CO keeps Ti in the surfacel ayer. Conversely,t he self-diffusion barrierf or an Al adatom on Al(111)i so nly [30] approximately 0.04 eV,m uch smaller than the barrierf or Hd iffusion [24,31] (0.15 eV), or Hs pillover from subsur-Alane (AlH 3 )i saunique energetic material that has not found ab road practical use for over 70 years because it is difficult to synthesize directly from its elements.…”
Section: Introductionmentioning
confidence: 95%
“…Some studies [22,24,26] have proposed that subsurface Ti can be more active than surface Ti in alane formation because of the lower barrier for H-spillover to Al by avoiding the formation of strong Ti-H bonds that hinder alane formation. However, when H-coverage is high and the surface Al can be continuously consumed, Ti tends to segregate to the surface and form a strong bond with the H. As reported by a recent study [29] of a Ti-doped Al(111) surface as a potential heterogeneous catalyst for hydrogenation reactions, it has been found that the adsorption of H and CO keeps Ti in the surface layer. On the other hand, the self-diffusion barrier for an Al adatom on Al(111) is only [30] ~0.04 eV, much smaller than the barrier for H-diffusion [24,31] (0.15 eV), or H-spillover from subsurface Ti (0.23 eV) [22] and surface Ti (0.7 eV [24] to 0.9 eV [22] ).…”
Section: Introductionmentioning
confidence: 95%